Implementasi LKS IPA Terpadu dalam Model Pembelajaran Generatif untuk Meningkatkan Kompetensi Peserta Didik Kelas VIII SMP - Sulpiana Sulpiana; Akmam Akmam; Zulhendri Kamus (Universitas Negeri Padang, 2018)
Student worksheet have been applied at school but it’s implementation in the learning is not optimum yet. Hence, the students competence are still low. The result of the students learning will be more optimum with the implementation of teaching material which is able to increase students motivation to study. Hence, this research aims to see the effect of student worksheet implementation with generative learning model material to the students competence at SMPN 7 Padang. The Type research of Quasi experiment with Non Equvalen Control Group design. The population of this research are the VIII grade students of SMPN 7 Padang in the 2017/2018 academic year. The sample taken with Purposive Sampling Technique. The instrument of this research is the objective tes for the knowledge competence, attitude competence, and the assignment sheet for work and skill competence. The hipotesis of this research tested with test the similarity of two average. The Type of this research result are : 1) the average of the knowledge compentence in the experiment class is 82.82, is higher than the control class 76.53. 2) the average of the manner compentences in the experiment class is 82,71is higher than the conrol class 80,09. 3) the average of the creativity competence in the experiment class is 84.00, is higher than the control class 79.00. to conclude the result of this study is there are several significant influence of the students worksheet implemention with the generative leaning in the students of SMPN 7 Padang compentence.